The role of surgery on primary site in metastatic upper urinary tract urothelial carcinoma and a nomogram for predicting the survival of patients with metastatic upper urinary tract urothelial carcinoma. (14th October 2021) - Zhang, Xiaodi; Wang, Ping; QI, Kaiyan; Qiao, Qiao; Jiang, Yuanjun
Abstract: Metastatic upper urinary tract urothelial carcinoma (mUTUC) is a relatively rare urothelial carcinoma, and little attention has been given to it. Our study established a nomogram by analyzing the prognostic factors of mUTUC to predict the survival of patients and revealed that the role of surgery at the primary tumor site. We extracted our data (2010–2016) from the Surveillance, Epidemiology, and End Results (SEER) database, and 628 patients with distant metastasis were identified. Propensity score matching (PSM) was used to balance the clinical variable bias in a 1:1 ratio. After PSM, we enrolled 502 patients in our study cohort. Univariate and multivariate Cox regression analyses and Kaplan–Meier curves showed that T stage, N stage, hepatic metastasis, surgery, and chemotherapy were prognostic factors for mUTUC before and after PSM. Based on the findings, a nomogram was constructed to predict the 12‐month survival of patients with distant metastasis. The analysis of subgroups of T stage, N stage, and different metastatic sites demonstrated that the survival of patients with T1/T2, N0/N1/N2/N3, metastasis including liver, and metastasis including bone could be improved by a combination of surgery and chemotherapy, while for the patients with T3/T4/TX, NX, metastasis including lung, and metastasis including distant lymph nodes, chemotherapy alone was a better choice to improve their overall survival. Radiotherapy has been proven to be useful for patients with N1/N2/N3 stage. We have provided more precise treatment strategies for stage IV patients. Our research fully affirms the role of surgery on primary site in UTUC patients with distant metastasis and the significance of classifying the patients into subgroups by integrating variables including T stage, N stage, and different metastatic sites to select the optimal treatment method. Abstract : It is a research about prognostic factors of metastatic upper urinary tract urothelial carcinoma (mUTUC) including metastatic patterns, therapy modes, and T/N stage based on the data extracted from SEER database. It reveals that the role of surgery on primary site is significant in the treatment of metastatic upper urinary tract urothelial carcinoma.